1364. Providing preventative care during the SARS-CoV-2 pandemic: Street medicine interventions amongst those experiencing unsheltered homelessness in the City of Detroit. (15th December 2022) - Joshi, Seema; Mann, Yasmeen; Petersen, Anneliese; Small, Eliana; Ayyar, Iven T; Abadejos, Justin R; Venable, Stephen; Ilagan, Roxanne; Ho, Brandon H; Shallal, Anita; Chen, Anne; Zervos, Marcus; et al.
Abstract: Background: In 2021, there were approximately 1300 people on a given day who have experienced homelessness within the city of Detroit, Michigan. Sheltered beds within the 24 homeless shelters in the city were drastically cut in half during the COVID-19 pandemic due to concerns of overcrowding perpetuating SARS-CoV-2 outbreaks. We aimed to describe the outreach efforts made by Street Medicine Organizations (SMO) of Detroit during the SARS-CoV-2 pandemic, highlighting infection prevention and control strategies, and promotion of COVID-19 vaccinations amongst the unsheltered homeless. Methods: Health promotion interventions were directed at individuals who were unsheltered (defined as those living on the streets of Detroit, encampment sites and abandoned buildings). Education, which was provided through in-person sessions, as well as targeted COVID-19 informational pamphlets were distributed with every street-based run. Hygiene kits, which included masks, hand sanitizer and gloves were distributed thrice weekly at shelters and encampment sites. Since access to hand hygiene was drastically limited, the SMO constructed 10 hand washing stations throughout the city. COVID-19 vaccination in people experiencing homelessness started in April 2021. Results: SMO prioritized a 60 square mile range within the city of Detroit, providing care to approximately 500 persons over the months of April 2020 to April 2021. Demographics for this population varied; age ranged from 23 to 76 years old, sex was 70% males, race were 67% Black, 29% White and 4% Hispanic. More than 2000 hygiene kits were distributed throughout this period. Ninety-one individuals experiencing unsheltered homelessness were provided the COVID-19 vaccine in April 2021. Conclusion: Individuals experiencing unsheltered homelessness face unique challenges to accessing timely medical care, which has been further exacerbated during the pandemic. These individuals have limited or no access to necessary measures needed to prevent the spread and severity of diseases of SARS-CoV-2. We describe a focused and effective approach to preventing infection among these individuals as a model for organizations nationally. Disclosures: All Authors : No reported disclosures.